Molecular characterization of cystic fibrosis in Macedonia : doctoral Thesis - Petreska, Lidija (L. Petreska, 1996)
Abstract: Cystic fibrosis (CF) is a common cause of childhood death, inherited in an autosomal recesive mode. Its incidence is estimated to be approximately 1 in 2500 among the Caucasian population [1]. The major clinical symptoms are result of structural changes and gradual loss of function of the secretory epithelial cells (specially the pancreatic cells), and a susceptibility of the lower respiratory airways to severe and chronic infections, because of an abnormality in the transmembrane transport for chloride ions. The gene responsible for CF was identified and characterized in 1989 by the techniques of "reverse genetic" and was called cystic fibrosis transmembrane regulator (CFTR) gene [9-11].